Clinical Features and Prognosis Analysis of Hormone Receptor-Positive, HER2-Negative Breast Cancer with Differential Expression Levels of Estrogen and Progesterone Receptors: A 10-Year Retrospective Study - Jin Liu; Mingyu Gan; Zijing Lin; Qin Deng; Juan Deng; Bin Zeng; Yanling Shi; Jia Ming (The Breast Journal)
Background. Estrogen and progesterone receptor status can predict breast cancer patient prognosis and treatment sensitivity, but research on low ER and PR levels and expression balance remains limited. Methods. From January 2010 to October 2016, 283 ER+/PR+/HER2-breast cancer patients who met the inclusion criteria were enrolled and divided into the H group (ER > 10%, N = 261) and the L group (1% ≤ ER ≤ 10%, N = 22). Groups were further divided into the HH group (ER > 10%/PR > 20%, N = 201), the HL group (ER > 10%/ER 1% ≤ PR ≤ 20% PR, N = 60), the LH group (1% ≤ ER ≤ 10%/PR > 20%, N = 5), and the LL group (1% ≤ ER ≤ 10%/1% ≤ PR ≤ 20%, N = 17). The LH group was excluded due to its small size, leaving the clinical and prognostic characteristics of 2 large groups and 3 subgroups to be analyzed. Results. L group patients had significantly more stage N2 axillary lymph nodes than H group patients (31.8% vs. 9.2%, P = 0.007). Age (P = 0.011), menopause status (P = 0.001), and tumor size (P = 0.024) were significantly different in the HL vs. HH and LL groups. Five-year DFS (94.6% vs. 77.0%, P < 0.001) and 5-year OS (97.2% vs. 85.8%, P = 0.001) rates significantly differed between HH and HL. No significant differences in 5-year DFS (77.0% vs. 81.9%, P = 0.564) or 5-year OS (85.8% vs. 87.8%, P = 0.729) rates were observed between HL and LL; the OS rates of HL and LL were similar. Conclusion. In the group of ER+/PR+/HER2-patients, there was no significant prognostic difference between ER-low positive and ER-high positive groups, but low PR expression was significantly associated with a worse prognosis. The role of ER and PR balance in breast cancer progression and individualized treatment requires further investigation.